2016
DOI: 10.22159/ijcpr.2016v8i4.15272
|View full text |Cite
|
Sign up to set email alerts
|

Allamanda Cathartica Linn.: Extraction and Pharmaceutical Evaluation of Various Extracts of Leaves and Flowers

Abstract: Objective: Extraction and evaluation of the antifungal activity of extracts from leaves and flowers of Allamanda cathartica (Apocynaceae) Linn.Methods: Leaves and flowers of A. cathartica were collected, dried and extracted by using well-established methods for alkaloids, flavonoids, steroids and crude extracts in polar and non-polar solvents. Extracts were screened for antifungal activity using ‘Disc Diffusion Assay’ against Candida albicans (Yeast), Aspergillus flavus and Tricophyton mentagrophyte (fungi). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
1
0
1
Order By: Relevance
“…It was noticed that the leaf extracts showed the best activity against K. pneumoniae as compared to other pathogens. 52 In another study, researchers have reported the antibacterial effects of avonoids (Quercitrin), isolated from A. cathartica plant, against Staphylococcus aureus (S. aureus; Grampositive) and E. coli (Gram-negative) bacterial strains. It was noticed that the isolated compound specically exhibited better antibacterial effects (higher zone of inhibition) against the Gram-negative strain as compared to the Gram-positive strain.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It was noticed that the leaf extracts showed the best activity against K. pneumoniae as compared to other pathogens. 52 In another study, researchers have reported the antibacterial effects of avonoids (Quercitrin), isolated from A. cathartica plant, against Staphylococcus aureus (S. aureus; Grampositive) and E. coli (Gram-negative) bacterial strains. It was noticed that the isolated compound specically exhibited better antibacterial effects (higher zone of inhibition) against the Gram-negative strain as compared to the Gram-positive strain.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Os extratos das folhas apresentaram importante efeito antibacteriano contra organismos patogênicos, sendo estes, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae e Proteus mirabilis. Além de mostrar potencial antifúngico contra cepas de Candida albicans, atividade que foi atribuída a ação dos compostos das classes de alcaloides, esteróis e flavonoides presentes nas folhas (Fartyal, 2016).…”
Section: Apocynaceae: Medicinais E Ornamentais 21 Allamanda Cathartica Lunclassified